Development of 27 new microsatellite markers for the shanny Lipophrys pholis - Jeannot, Laura-Li; Mouronvalle, Clara; Peyran, Claire; Blanco, A.; Planes, S, E (Molecular Biology Reports, 2022)
International audience Background: The shanny Lipophrys pholis is an intertidal fish that is widely distributed throughout the Northeast Atlantic. Characterized by limited adult mobility and a long pelagic larval duration, the shanny stands as an ideal model to better understand larval dispersal and connectivity dynamics, which are critical parameters with implications for marine conservation and management.Methods and results: To this aim, we developed 27 highly polymorphic microsatellite markers and characterized a population of 42 individuals, presenting an average allelic diversity of 20.1 alleles per locus and heterozygosity ranging from 0.619 to 1.Conclusions: This set of newly developed microsatellite markers will be useful in providing critical insights into the processes which shape L. pholis gene flow and connectivity patterns and can be used to investigate local parentage lineages.